Diagenetic origin of nodules in the Sheepbed member, Yellowknife Bay formation, Gale crater, Mars. Issue 7 (22nd July 2014) - Stack, K. M.; Grotzinger, J. P.; Kah, L. C.; Schmidt, M. E.; Mangold, N.; Edgett, K. S.; Sumner, D. Y.; Siebach, K. L.; Nachon, M.; Lee, R.; Blaney, D. L.; Deflores, L. P.; et al.
Abstract The Sheepbed member of the Yellowknife Bay formation in Gale crater contains millimeter‐scale nodules that represent an array of morphologies unlike those previously observed in sedimentary deposits on Mars. Three types of nodules have been identified in the Sheepbed member in order of decreasing abundance: solid nodules, hollow nodules, and filled nodules, a variant of hollow nodules whose voids have been filled with sulfate minerals. This study uses Mast Camera (Mastcam) and Mars Hand Lens Imager (MAHLI) images from the Mars Science Laboratory Curiosity rover to determine the size, shape, and spatial distribution of the Sheepbed nodules. The Alpha Particle X‐Ray Spectrometer (APXS) and ChemCam instruments provide geochemical data to help interpret nodule origins. Based on their physical characteristics, spatial distribution, and composition, the nodules are interpreted as concretions formed during early diagenesis. Several hypotheses are considered for hollow nodule formation including origins as primary or secondary voids. The occurrence of concretions interpreted in the Sheepbed mudstone and in several other sedimentary sequences on Mars suggests that active groundwater systems play an important role in the diagenesis of Martian sedimentary rocks. When concretions are formed during early diagenetic cementation, as interpreted for the Sheepbed nodules, they have the potential to create a taphonomic window favorable for the preservation of Martian organics.